Mitigasi Risiko Pembiayaan Bermasalah pada Koperasi Jasa Keuangan Syariah yang Mengelola Unit Ritel: Pendekatan Syariah Compliance - Dede Saeroji; Dini Selasi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
The expansion of retail units by Sharia Financial Services Cooperatives (KJKS) serves as a business diversification strategy to improve members’ welfare. However, this expansion increases exposure to the risk of nonperforming financing (NPF). This study employs a qualitative literature review using secondary data from the Financial Services Authority (OJK) to analyze financing risk mitigation strategies through a Sharia compliance approach. The findings indicate that the national NPF rate for KJKS remains relatively high and is influenced by weak feasibility analysis and member moral hazard. The role of the Sharia Supervisory Board (DPS), the implementation of Standard Operating Procedures (SOPs) based on DSN-MUI fatwas, and an early warning system are key to risk mitigation. Strengthening Sharia audits by the OJK is recommended to ensure that KJKS retail units remain sound and compliant with Sharia principles.